Analisis Perbandingan Naghmah (nada) dan Tanghim (intonasi) dalam Syair “Al-i’itiraf” Karya Abu Nawas - Aliyah, Muna Ma’rudatul (Maliki Interdisciplinary Journal, 2025)
The poem Al-I’itiraf by Abu Nawas is one of the classical Arabic literary works filled with emotional and spiritual expressions. This study aims to analyze the comparison of tone and intonation in the poem using a phonetic (Ilmu Aswat) and prosodic linguistic approach. The study highlights how tone and intonation in Al-I’itiraf reflect profound meanings, emotions, and linguistic aesthetics conveyed by the poet. Trough phonetic analysis, it was found that variations is tone and intonation in the poem play a crucial role in emphasizing the spiritual message, particularly the expression of humility and seeking forgiveness from Allah. The study also reveals that certain intonation patterns in the poem create a strong rhetorical effect and emotionally influence the audience. The findings of this study not only contribute to understanding the phonetic beauty in Abu Nawas’ works but also enrich insights into the relationship between linguistic and aesthetics in classical Arabic poetry.